Elevated International Normalized Ratio (INR) is Associated With an Increased Risk of Intraventricular Hemorrhage in Extremely Preterm Infants. Issue 5 (July 2019) - Glover Williams, Alessandra; Odd, David; Bates, Sarah; Russell, Geoff; Heep, Axel
Abstract : Introduction: The international normalized ratio (INR), a standardized method of reporting the prothrombin time, can be a surrogate marker of the vitamin K-dependent coagulation pathways. Objective: To evaluate the relationship between INR measurements in the first 48 hours of life and subsequent development of intraventricular hemorrhage (IVH) in extremely preterm infants. Materials and Methods: A single-center retrospective, observational cohort study of infants born at <28 weeks gestation. The main outcome measure was defined as the degree of IVH seen on cranial ultrasound examinations at day 7 postnatal age. Results: Of 200 infants, 109 (mean gestational age, 25.2 wk [SD, 1.27]) had coagulation results available. Of 109, 26 developed IVH. Elevated INR was associated with increased risk of a severe IVH (odds ratio [OR] 6.50; 95% confidence interval [CI], 1.65-25.62; P =0.008) adjusted for gestation, birth weight, and sex. INR was significantly associated with severe IVH in infants who did not receive blood products (OR, 64.60; 95% CI, 1.35-3081.25; P =0.035), but not in those who did (OR, 2.93; 95% CI, 0.67-12.71; P =0.151) ( P interaction =0.086). Conclusion: An elevated INR in the first 48 hours of life may be useful to identify preterm infants at risk of severe IVH and may guide strategies to prevent the development, or limit the extension, of IVH. Abstract : Supplemental Digital Content is available in the text.